KOMPLEKSITAS HUBUNGAN ANTARA WAZAN DAN MAKNA (Kajian terhadap Variasi Wazan dan Ambiguitas Bentuk Kata dalam Bahasa Arab) - Sukamta Sukamta (Sunan Kalijaga State Islamic University Yogyakarta, 2012)
This paper discusses wazans, including those relating to i'lal and ibdal, in Arabic and the efforts to make the learning easier for the sake of reading the language orthography with no harakat. Wazans in Arabic are hundreds, but this paper only focuses on those related to changes in the word forms (tasrif istilahi), whose wazans of fi’il ma alone are 35. The writer classifies examples of words with the same wazan, and combines wazan ruba'i mujarrad and mazid as well as the mulhaq, as both have the same syakal. He also maps the words of the same wazan but different meaning because the sigah (the word form) is different. As to facilitate the words that have ibdal andor i'lal, the writer gives examples of such words, to be the benchmark for the search of other examples. To conclude, first is that mastery of wazans in Arabic is very important not only to read the orthography without the syakal, but also to determine the meaning of the word. Second, although a wazan determines the meaning of a word, but there is problem since the same wazan may have different meanings. Third, the knowledge of the context of the utterance will help determine the meaning of the word, and the meaning finally defines the word wazan. In other words, wazan will be determined by the meaning of the word, and vice versa, wazan and context determine the meaning of the word. Fourth, the triangle of context, meaning and wazan relate to each other and have a very important role in the process of reading and understanding texts, but not necessarily the same wazan shows the same form of words, and vice versa. This is where the complexity is.